Parents' Role in Disabled Athletes' Confidence in the National Paralympic Committee Indonesia, Magelang Regency (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2025)
This study aims to examine the role of parents in developing the self-confidence of athletes with disabilities who are affiliated with the National Paralympic Committee Indonesia (NPCI) in Magelang Regency. Self-confidence is a crucial psychological component that influences athletes’ performance, especially among individuals with disabilities who often face social, physical, and emotional challenges. A descriptive quantitative research design was employed, utilizing a closed-ended questionnaire as the main data collection instrument. The sample consisted of 20 parents of athletes with disabilities, selected using purposive sampling based on specific inclusion criteria. The questionnaire was tested for validity and reliability, resulting in 30 out of 35 items being declared valid, with a Cronbach’s Alpha coefficient of 0.959, indicating a high level of reliability. The analysis revealed that the overall parental role was categorised as "Good" to "Very Good," particularly in areas related to emotional support, attention, provision of nutrition, motivation, and creating a positive home environment. The results suggest that consistent and meaningful parental involvement plays a significant role in enhancing the self-confidence of disabled athletes, which in turn supports their participation, perseverance, and achievements in sports training and competitions. These findings underscore the importance of family-based support systems in disability sports development.